PERSEPSI PELANGGAN APOTEK K-24 TAMAN GALAXCY KOTA BEKASI - Tommy Adhianto; Ismail Razak (Jurnal Ekonomi dan Industri, 2024)
The aim of this study is to know the perception of customers of Apotek K-24 Taman Galaxcy Kota Bekasi. Primary data is obtained from customers of Apotek K-24 Taman Galacxy Kota Bekasi through admission filling of questionnaire by using scale of Likert. In this study, purpose sampling method is used. Data analysis method is descriptive analysis and semantic differential analysis. The result of this study indicated that customers of Apotek Taman Galaxcy Kota Bekasi agree with all points of the statement.